First UK use of the iTClamp™ haemorrhage control system: Case report. (July 2014) - Hudson, Anthony; Glazebrook, William
We present two cases of the use of a new device for external haemorrhage control, the iTClamp™ (Innovative Trauma Care, Inc., Edmonton, Canada). These are the first uses of the devices in the UK and the first times worldwide it has been used to control haemorrhage from the neck.